On-object gain penalty of RFID tags mounted on car glass - Pineda, Edwin (2016)
This paper presents a study on the identification of main parameters involved in the on-object gain penalty for RFID Tags when are used over front glass of vehicles. We assess four variables with relevant importance over this penalty: Glass type, polarized film, polarization of the electromagnetic wave, and the tag type. The assessment is performed using experimental tests based in the Design of Experiment technique. From the results, a simplified model to determine the on-object gain penalty is developed.